Study guides

☆☆

Q: What is the expression for the sum of -2 and 6 and 7?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

0*9*7*2*6 = 9*6*7*2*0

4 and 3(4 + 3 = 7)or 1 and 6(1 + 6 = 7)or 5 and 2(5 + 2 = 7)

On two 6-sided fair dice:Rolling a sum of 5: 4 out of 36, or 11.11%Rolling a sum of 7: 6 out of 36, or 16.67%Rolling a sum of either 5 or 7: 10 out of 36, or 27.78%Here's why: Look at the dice as unique, (maybe one is red and one is blue). Then there are 36 different possible outcomes.The four that give a sum of 5: 1+4, 2+3, 3+2, 4+1.The six that give sum of 7: 1+6, 2+5, 3+4, 4+3, 5+2, 6+1So there are 4 chances out of 36 (or 1 out of 9 = 11.11%) to get a sum of 5, and 6 chances out of 36 (or 1 out of 6 = 16.67%) to get a sum of 7. If you want either 5 or 7 as a sum, add the chances together to get 10 out of 36 (or 5 out of 18 = 27.78%)

It is 9*(n + 7)

mean=Sum of all observations(divided by)number of observations = 2+5+7+6(by)4 = 20(by)4 = 5

Related questions

It is (12 + 6) - 7

The expression (not equation) is 6 + 7

2(n+7)

7 * (c + 2) = 7 * c + 14

0*9*7*2*6 = 9*6*7*2*0

An expression is the sum (or difference) of two or more terms. Example 3x + 2y is an expression.It is a mathematical statement e.g 7=6+1 THE WHOLE THING IS AN EQUATION but the 6+1 is a expression.You can only have an expression if there is not an = signYes the 6 + 1 part is an expression. If you have an = sign or any of the other inequality symbols (,...) it is no longer an expression but a full math sentence.

It depends. Is the entire expression squared or just radical 7?Assuming the latter, then 6 + (√7)^2 = 6 + 7 = 13.

7

GCF(7, 42) = 77 = 7*1 and 42 = 7*6 So 7 + 42 = 7*(1 + 6).

There are 36 permutations of two dice. Of them, 6 have a sum of 7, (1+6, 2+5, 3+4, 4+3, 5+2, and 6+1) and 2 have a sum of 11 (5+6 and 6+5). The probability, then of getting a sum of 7 or 11 is (6 plus 2) in 36, or 8 in 36, or 2 in 9, or about 0.2222.

20

14/3 + 4 = 14/7 = 2

People also asked